PERFORMANCE ANALYSIS OF ORGANIZATIONAL EFFECTIVENESS IN THE GOVERNMENT - Veni Devialesti (University of Sang Bumi Ruwa Jurai, 2020)
Good governance is a prerequisite for effective government formation. For this reason, a competent apparatus is needed to improve its performance so that governance can run optimally. Performance is the result of work in quality and quantity achieved by an employee in carrying out his duties in accordance with the responsibilities given to him, Mangkunegara (2007).The purpose of this study was to determine the effect of effectiveness on employee performance in Bandar Lampung City Government .Based on the results of the study found Variable organizational effectiveness is a very effective variable to improve employee performance.